Green starch nanoparticles production in situ using α-amylase from a newly isolated Bacillus subtilis strain-MA6: statistical designs and characterizations - Mohamed S. Hasanin; Mohamed A. A. Abdella (Microbial Cell Factories)
Abstract Background Starch is a carbohydrate polymer, made up of multiple glucose units, connected through glycosidic bonds. Starch nanoparticles (StNPs) are characterized as particles that possess at least one dimension measuring less than 1000 nm, while still being larger than a single molecule, and they have several uses in diverse technological fields. Various studies indicate that synthesizing StNPs through physical and chemical techniques is expensive, requires a lot of energy, and may harm human health and the environment. In contrast, the enzymatic synthesis of StNPs exerts milder impacts on the final products, rendering them more eco-friendly, safe, and healthier. So, amylases can produce StNPs with enhanced solubility, gelation, and viscosity characteristics by hydrolyzing soluble starches. Results This study explores the production of starch nanoparticles (StNPs) by α-amylase enzyme in situ from a newly isolated bacterial strain, which was biochemically described, genetically identified, and deposited into the database of GenBank under the designation Bacillus subtilis strain-MA6 (accession number: ON840082). The production medium was adjusted by employing statistical optimization of several parameters using the Plackett-Burman design (P-BD) and Box-Behnken design (B-BD) of the response surface methodology (RSM). Optimization of medium parameters using P-BD and B-BD models caused a 14.5-fold increase in α-amylase production. The StNPs were synthesized from bulk starch using three different α-amylase activities. Based on the B-BD results, trial 5 (B-BD/T5), trial 7 (B-BD/T7), and trial 13 (B-BD/T13) were selected for the StNPs characterization using Fourier-transform infrared spectroscopy (FTIR), Dynamic light scattering (DLS), and high-resolution transmission electron microscopy (HR-TEM) analysis. Trial 13 represented the highest α-amylase activity and observed high stability with an average zeta potential of about − 15.1 ± 3.2 mV. Moreover, HR-TEM showed the StNPs as spheres with an average size of about 43 nm. Conclusion StNPs were synthesized from bulk starch using the B. subtilis strain-MA6 α-amylase enzyme. The concentration of α-amylase plays a role in converting bulk starch to nanosized particles, which affects the stability of the produced nanoparticles and their size. This observation offered an optimistic technique to produce StNPs via a green and eco-friendly process. Graphical abstract